Security Analysis of Pedestrian Comfort on the Use of Pedestrian Paths in the Bung Hatta Palace Area - Angelalia Roza; Yessy Yusnita; Alfad Azhar (Journal of Technology Informatics and Engineering, 2024)
Many pedestrian paths are still not well organized and optimally utilized. On the other hand, the comfort of pedestrian paths should be a priority in urban transportation planning. This study aims to determine the level of pedestrian service on Jl. Istana and Jl. H. Agus Salim Bukittinggi city and to determine the perceptions of people who use pedestrian crossing facilities on Jl. Istana and Jl. H. Agus Salim in the Bung Hatta Palace area Bukittinggi based on comfort and level of pedestrian service. This research uses descriptive research methods carried out to explain the situation that occurs on the pedestrian path Jl. Istana and Jl. H. Agus Salim in the Bung Hatta Palace area Bukittinggi. For the results of pedestrian movement characteristics obtained data Flow (Flow) in segment I amounted to 0.12, 0.70 and 0.75 pedestrians / min, in segment II amounted to 0.29, 1.13 and 1.67 pedestrians / min. Speed data in segment I was found to be 52.32, 55.97 and 54.97 m/min, in segment II it was 55.03, 51.74 and 53.96 m/min. Density in segment I was 0.18, 0.19 and 0.18 m2/ped, in segment II it was 0.62, 0.57 and 0.60 m2/ped. Space in segment I was 5.65, 5.38 and 5.50 m2/ped, segment II was 1.62, 1.74 and 1.67 m2/ped. Pedestrian ratio in segment I amounted to 0.0016, 0.0094 and 0.0100, segment II amounted to 0.00380, 0.01509 and 0.02227. The results showed that the level of pedestrian service on Jl. Istana and Jl. H. Agus Salim in the Bung Hatta Palace area Bukittinggi is A, because pedestrians can move freely according to their wishes without any interference from other pedestrians and for the results of the questionnaire that has been distributed as many as 100 respondents obtained a comfort value of 72% and this figure is included in the comfortable category.